Axel Honneth: the social conflict and the ways of the look. Notes to think the problem beyond recognition - Palacio, Jorge Ariel (Revista de Humanidades de Valparaíso, 2021)
In this paper we will address one of the forms that assume the social conflict, considering an everyday behavior: the look and the ways of representation that it produces. The beginning of our argumentation is marked by Axel Honneth’s theory of recognition. His contributions give a perspective that allow us to unite the analysis of socials struggles with the problem of the look. For this work we study how Honneth build an ethical approach about the look, from the ideas of recognition and inter-subjectivity. In that sense, practical behavior like social humiliation and social domination, materialized through the look, are read as the negative reverse of recognition. We seek to think the look inserted in the social conflict beyond recognition, because we defend the hypothesis that the notion of recognition, as proposed by Honneth, assumes normative assumptions that visualize conflict as oriented to the consolidation of a mediated understanding of one`s own personality and the self-affirmation of subject, as also assumes an evolutionary logic rationality. Once shown this, we will answer the question: how to understand/comprehend the problem of the look from a different perspective?